ChemInform Abstract: Ninhydrin in Synthesis of Heterocyclic Compounds. Issue 34 (August 2015) - Ziarani, Ghodsi Mohammadi; Lashgari, Negar; Azimian, Fereshteh; Kruger, Hendrik G.; Gholamzadeh, Parisa
Abstract Review: 537 refs.